P.59: New Synthesis of Novel Phosphor for LED Technology: Synthesizing Sr3Y2(BO3)4:Eu2+ From Strontium Borate Precursors. Issue 1 (1st July 2013) - Kilburn, Troy B.; Way, Zachary K.; Orme, Patrick; Diaz, Anthony L.
Abstract Doping Eu2+ is challenging in some materials because of the stability of Eu3+. An alternative method for doping divalent europium was explored in the phosphor Sr3B2O6:Eu. Sr3B2O6:Eu has been synthesized with a mixture of divalent and trivalent emission. Here, samples prepared by traditional‐methods are compared to samples prepared using a SrB4O7:Eu precursor.